The Effect of Relative Performance Information on Performance and Effort Allocation in a Multi-Task Environment - Hannan, R. Lynn; McPhee, Gregory P.; Newman, Andrew H.; Tafkov, Ivo D. (The Accounting Review, 2013)
ABSTRACT This study investigates how relative performance information (RPI) affects employee performance and allocation of effort across tasks in a multi-task environment. Based on behavioral theories, we predict that the social comparison process inherent in RPI induces both a motivation effect that results in increased effort as well as an effort distortion effect that results in the distortion of effort allocations across tasks away from the firm-preferred allocations. We also predict that both effects are magnified when the RPI is public compared to private. We argue that although the motivation effect will generally benefit performance, the effort distortion effect may be detrimental to performance. We design an experiment that isolates these two effects. Consistent with our predictions, we find that RPI induces both motivation and effort distortion effects and that both effects are magnified when the RPI is public rather than private. Although the motivation effect increases performance, we demonstrate that the effort distortion effect can decrease performance. By isolating the motivation and effort distortion effects, our study provides insights into the costs and benefits of RPI in a multi-task environment. As such, it informs accountants regarding the design of information systems and when tasks should be aggregated or disaggregated across employees. Data Availability: Data are available from the authors upon request.